Studi Kualitas Pelayanan Nasabah Pada Bank Mandiri Area Semarang Pahlawan - Sutanto, Inggrid Benedicta; Sukresna, I Made (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
The objectives of this study are: (1). Assessing customer service quality in the aspects of tangibles, reliability, responsiveness, assurance, and empathy; (2). Assessing ways to increase customer satisfaction in order to achieve or exceed service targets. The type of data used is primary data which comes from 2 (two) groups of informants, namely customers and employees, with a purposive sampling method. The analysis tool uses a pure qualitative descriptive approach. The results of the study prove that: Customer satisfaction with the services provided by Bank Mandiri Semarang Pahlawan area regarding the dimensions of tangibles, reliability, responsiveness, assurance, and empathy is at the level of confirmation or satisfaction. Furthermore, how to increase customer satisfaction in order to achieve or exceed service targets by providing more attractive facilities, the number of front liner officers and queuing seats added, strategies to stay on time and fulfill obligations as marketing, increase cooperation with all departments.